Labor under siege : Big Bob McEllrath and the ILWU's fight for organized labor in an anti-union era - Schwartz, Harvey, 1939-; Magden, Ronald (University of Washington Press, 2022)
"At six feet four inches and with a powerful speaking style, Big Bob-Robert McEllrath's waterfront handle-was heralded for his charisma, unifying vision, and negotiating prowess. President of the International Longshore and Warehouse Union (ILWU) for twelve eventful years, McEllrath retired in 2018 after nearly forty years as a union officer. More than a biography of a storied career, Labor under Siege explores how the influential union persisted in an era when the US labor movement was under attack and seemingly in retreat. In the face of grave dangers since the 1980s, including threats from corporations, government authorities, law enforcement agents, and even other labor unions, the ILWU has persevered and retained its vibrancy. Offering insight into Big Bob's leadership and a close-up view of how decision-making and policy were carried out to ensure the union's survival, Labor under Siege shows how union officers and rank-and-file members shaped ILWU strategy and furthered the union's legacy of advocating for workers' rights, democracy, and justice"--